Evaluation of Coastal Management in the Municipality of Paulista/PE in the Light of the Decalogue - Lucena de Godoy Maciel, Ana Luiza; Paes Barreto, Eduardo; Assunção da Silva, Carlos Fabricio; Miranda dos Santos, Maria Pricila; de Vasconcelos Santos, Priscila Fernanda (Anuário do Instituto de Geociências, 2024)
Brazil adopts Integrated Coastal Management as a way of protecting coastal environments through sustainable use and through the National Coastal Management Plan – PNGC structures actions directed at coastal areas, guaranteeing municipalities a prominent position in the integrative process. The structuring of the legal and institutional framework does not remove the picture of degradation borne by coastal cities, which have problems with sanitation, erosion and reduction of biodiversity. The general objective of this article is to analyze the Coastal Management process adopted by the municipality of Paulista, Pernambuco, in order to provide subsidies for institutionalization and sustainable governance. The methodology was structured in two parts. The first part used the Land Use and Land Cover (LULC) dataset available free of charge MapBiomas collection 6. The second part used the methodology proposed by Barragán in the “Decalogue for the Management of Coastal Areas”, where the 10 indicators are analyzed fundamental to evaluate actions related to coastal management. The methodology was adapted to include the mapping of the use and occupation of the municipality's coastal area over a period of 36 (thirty-six) years. The results of the analysis of land use and occupancy indicate a steady growth in anthropized areas from 1986 until the end of the 1990s, stabilizing with few changes. After an increase, there was a new stabilization between 2006 and 2012, followed by a notable growth in 2013–2014 and a subsequent period with less pronounced increments until the year 2021. Regarding the matrix analysis, there is a greater advancement in aspects related to Knowledge and Information, Normative and Competencies, whereas items such as Training and Capacity Building, Resources, and Public Policies require better strategic definitions by the municipality. As for the results of the matrix analysis, they reveal the need for the implementation of impact mitigation measures, the strengthening of oversight and monitoring, the development of strategies for climate change adaptation, the promotion of environmental education, and the fostering of scientific research in coastal areas. Finally, there is a suggestion for the continuous evaluation and correction of actions related to coastal and marine areas of the municipality, as well as the use of scientific evidence in decision-making.